Mobilization of intracellular calcium by intracellular flash photolysis of caged dihydrosphingosine in cultured neonatal rat sensory neurones - Ayar, Ahmet; Thatcher, Nicola M.; Zehavi, Uri; Trentham, David R.; Scott, Roderick H. (Acta Biochimica Polonica, 1998)
The ability of dihydrosphingosine to release Ca2+ from intracellular stores in neurones was investigated by combining the whole cell patch clamp technique with intracellular flash photolysis of caged, N-(2-nitrobenzyl)dihydrosphingosine. The caged dihydrosphingosine (100 ?M) was applied to the intracellular environment via the CsCl-based patch pipette solution which also contained 0.3% dimethylformamide and 2 mM dithiothreitol. Cultured dorsal root ganglion neurones from neonatal rats were voltage clamped at -90 mV and inward whole cell Ca2+-activated currents were recorded in response to intracellular photorelease of dihydrosphingosine. Intracellular photorelease of dihydrosphingosine (about 5 ?M) was achieved using a Xenon flash lamp. Inward Ca2+-activated currents were evoked in 50 out of 57 neurones, the mean delay to current activation following photolysis was 82 ± 13 s. The responses were variable with neurones showing transient, oscillating or sustained inward currents. High voltage-activated Ca2+ currents evoked by 100 ms voltage step commands to 0 mV were not attenuated by photorelease of dihydrosphingosine. Controls showed that alone a flash from the Xenon lamp did not activate currents, and that the unphotolysed caged dihydrosphingosine, and intracellular photolysis of 2-(2-nitrobenzylamino) propanediol also did not evoke responses. The dihydrosphingosine current had a reversal potential of -11 ± 3 mV (n = 11), and was carried by two distinct Cl- and cation currents which were reduced by 85% and about 20% following replacement of monovalent cations with N-methyl-D-glucamine or application of the Cl- channel blocker niflumic acid (10 ?M) respectively. The responses to photoreleased dihydrosphingosine were inhibited by intracellular application of 20 mM EGTA, 10 ?M. ryanodine or extracellular application of 10 ?M dantrolene, but persisted when Ca2+ free saline was applied to the extracellular environment. Intracellular application of uncaged dihydrosphingosine evoked responses which were attenuated by photolysis of the caged Ca2+ chelator Diazo-2. Experiments also suggested that extracellular application of dihydrosphingosine can activate membrane conductances. We conclude that dihydrosphingosine directly or indirectly mobilises Ca2+ from ryanodine-sensitive intracellular stores in cultured sensory neurones.
Keywords: Caged sphingolipid; Cultured neurones; Dihydrosphingosine; Intracellular calcium; Intracellular signalling; Ryanodine